2011
DOI: 10.1007/s10964-011-9682-2
|View full text |Cite
|
Sign up to set email alerts
|

The Familial Context of Adolescent Language Brokering Within Immigrant Chinese Families in Canada

Abstract: Language brokering, whereby children of immigrants provide informal translation and interpretation for others, is considered commonplace. However, the research evidence remains inconsistent concerning how language brokering relates to the psychological health of child language brokers and their relationships with their parents. Furthermore, few studies have examined the familial context as an explanation source. This study evaluated the moderating effects of adolescents' support of family obligation values and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 38 publications
4
33
0
1
Order By: Relevance
“…Adolescents’ sense of alienation from parents intensified the effects of feelings about translating for parents on adolescent depressive symptoms. These results are in line with prior studies demonstrating the importance of the parent–child context in the association between language brokering and adolescent outcomes (Hua & Costigan, ; Love & Buriel, ; Weisskirch, ). In a parent–child relationship with a high sense of alienation, parents tend not to display empathy, warmth, and support toward the child (Chao, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Adolescents’ sense of alienation from parents intensified the effects of feelings about translating for parents on adolescent depressive symptoms. These results are in line with prior studies demonstrating the importance of the parent–child context in the association between language brokering and adolescent outcomes (Hua & Costigan, ; Love & Buriel, ; Weisskirch, ). In a parent–child relationship with a high sense of alienation, parents tend not to display empathy, warmth, and support toward the child (Chao, ).…”
Section: Discussionsupporting
confidence: 92%
“…In the case of language brokering, one important contextual factor may be the parent-child relationship context (Morales & Hanson, 2005;Weisskirch, 2007Weisskirch, , 2013Wu & Kim, 2009). For example, Hua and Costigan (2012) demonstrated that, in an especially unsupportive parent-child relationship context, adolescents are more susceptible to the negative effects of language brokering on their adjustment. As for personal attributes, the trait of resilience-the ability to bounce back from a negative experience-has been shown to be a key factor relating to how individuals go through adverse situations (Connor & Davidson, 2003;Fredrickson, Tugade, Waugh, & Larkin, 2003).…”
mentioning
confidence: 99%
“…Language brokering refers to assistance that children provide their immigrant parents in translating and interpreting written or spoken, formal or informal, cultural material from the culture of destination (Chao, 2006). Language brokering might benefit children’s cognitive and emotional development (Hua & Costigan, 2012) because it is associated with greater biculturalism and academic performance (Buriel, Perez, DeMent, Chavez, & Moran, 1998), higher ethnic identity and cultural value endorsement (Weisskirch et al, 2011), enhanced perspective taking and greater empathic concern (Guan, Greenfield, & Orellana, 2014), and greater respect for mothers and fathers (Chao, 2006). However, language brokering also confers risks on children by placing too much responsibility on them or exposing them to sensitive personal information about a parent or themselves.…”
Section: Specificity Principle: Domainmentioning
confidence: 99%
“…Much research has examined language brokering with an eye to how it affects child development (see, for example, Buriel et al, 2006; Chao, 2006; Dorner et al, 2007; Hua and Costigan, 2012; Orellana, 2009). This work makes clear the anxiety the practice provokes for adults about children somehow being “out of place,” in danger of being exposed to things beyond their years, and carrying burdens that children presumably should not assume.…”
Section: “Non-normative” Childhoods: Child Language Brokeringmentioning
confidence: 99%